Collaboration of the Family and the School in Prevention of Adolescent Delinquent Behaviour - Žygaitienė, Birutė; Veličkienė, Jolanta (Pedagogika, 2016)
The aim of the research was to identify ways of support provided by the school to the family implementing prevention of adolescent delinquent behaviour. The research was carried out in general education institutions in 2014. The sample of the research included 321 adolescents, 150 parents, 62 teachers and 5 social pedagogues. The obtained empirical research data were processed using statistical, graphical and correlation analysis. The research revealed that the most frequent manifestations of adolescent delinquent behaviour are related to run around and use of swear words, absenteeism and refusal to prepare homework. The majority of parents and teachers allocate the most considerable attention to individual collaboration forms, which make better understanding of the family possible. Such forms embrace parents’ meetings, telephone and individual conversations, joint events, trips, seminars and projects. About half of the parents and teachers in the survey pointed out that they communicate via telephone, exchange SMSs and e-mails. Ongoing collaboration occurs on the electronic school gradebook. The acquired data also revealed that attending adolescent’s home and individual conversations are among the most efficient forms for prevention of delinquent behaviour. Assurance of school attendance is considered to be one of the most significant factors. The majority of adolescents are sure that assurance of school learners’ safety at school is of importance. Close collaboration between the family and the school as well as active involvement of parents into adolescents’ life both at home and at school are seen as relevant factors.